Winter abundance of bowhead whales, Balaena mysticetus, in the Hudson Strait, March 1981 - Koski, William R.; Heide-Jørgensen, Mads Peter; Laidre, Kristin L. (J. Cetacean Res. Manage., 2023)
Satellite tracking studies of bowhead whales (Balaena mysticetus) in West Greenland and the eastern Canadian Arctic have documented that Hudson Strait is an important wintering ground for animals summering in the Baffin Bay-Davis Strait area and the Hudson Bay-Foxe Basin area. In light of this new information, data were re-examined on abundance of bowhead whales at this wintering ground derived from a systematic strip census survey conducted in March 1981. Three strata in Hudson Strait were covered by equally spaced north-south transect lines. Most sightings were in the western stratum, with one and none in the central and eastern strata, respectively. Abundance estimates were corrected for whales at the surface missed by observers using data from a similar survey in the Beaufort Sea. Corrections for whales submerged when the survey aircraft passed were developed using new data from time-depth recorders deployed on seven bowhead whales in Disko Bay, West Greenland, in April-May 2002-05. The fully corrected abundance estimate for the Hudson Strait in March 1981 was 1,349 (95% CI 402-4,529) whales. Similar surveys were conducted along West Greenland in March 1981 and 1982; the combined estimate was 1,549 (95% CI 589-4,072). Other unsurveyed areas in Baffin Bay may contribute an additional 8% to this combined estimate. The projected population size for both areas was 3,633 (95% CI 1,382-9,550) in 2004, assuming a population growth rate of 3.4% per year (George et al., 2004), which may not be appropriate for this population. However, increased sighting rates and traditional knowledge reports confirm that the population is growing. The use of availability and detection biases together with the restricted seasonal distribution of whales in March makes this the most complete estimate of this population in the 1980s to date.